Efficacy and safety of single dose of oral secnidazole 2 g in treatment of bacterial vaginosis: A systematic review and meta-analysis. (July 2019) - Elghazaly, Shrouk M.; Hamam, Khaled M.; Badawy, Marwa M.; Yakoub Agha, Nadim Aiman; Samy, Ahmed; Abbas, Ahmed M.
Abstract: Background: Bacterial vaginosis (BV) is a common disease characterized by vaginal discharge. Objective: To evaluate the evidence from published randomized clinical trials (RCTs) about the efficacy and safety of single dose of oral secnidazole 2 g in comparison with other drugs. Search strategy: Electronic databases were searched using the following MeSH terms (bacterial vaginosis OR vaginosis) AND (secnidazole OR secnol OR sabima OR secnidal OR minovage). Selection criteria: All RCTs assessing effect of secnidazole in treatment of BV were considered for this meta-analysis. Two-hundred thirty two studies were identified of which six studies were deemed eligible for this review. Data collection and analysis: The extracted data were entered into RevMan software. The relative risk (RR) and 95% confidence interval (CI) were calculated. The extracted outcomes were the clinical cure and adverse effects. Main results: The pooled estimate showed that ornidazole is superior to a single dose of oral secnidazole in clinical cure at the 4th week after treatment (RR = 0.81; 95% CI [0.73- 0.89], p < 0.0001, I 2 = 0%). There were no difference between secnidazole and metronidazole (RR = 0.97; 95% CI [0.90–1.05], I 2 = 0%, p = 0.5). Conclusions: Single oral dose of secnidazole 2 g doesn't differ from metronidazole regimen however, it may be inferior to ornidazole in treatment of BV.